Determinan Kepatuhan Konsumsi Tablet Tambah Darah Pada Remaja Putri Kelas X dan XI di SMK Tangerang - Janah, Riska Miftahul; Trimawartinah, Trimawartinah (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2025)
Background: Adolescent anemia is likely to increase from 2007 to 2023 with various factors causing anemia, the main one being low iron intake. Supplemental intake has been carried out by government intervention since ten years ago, but the program has not been thoroughly evaluated in terms of knowledge, attitude and peer support factors on adolescents adherence to taking supplemental blood tables. Methods: The study design used was a cross-sectional study in which direct interviews were conducted using gform during school learning time. The sampling technique adjusts the population of women aged 15-19 who have menstruated with a total population of 140 students. Data processing and analysis used statistical software where characteristic data were presented in the form of numbers and percentages, followed by relationship analysis with the chi-square test. Results: The percentage of students who were not compliant with taking blood supplement tablets was 107 (76.4%). Determinant factors that have a relationship with adherence to blood tablet consumption are the sense of side effects (p = 0.009, PR = 3.14) and family support (p = 0.011, PR = 3.05), while the factors of knowledge, refusal, motivation, teacher support and peer support do not have a direct relationship with adherence to blood tablet consumption. Conclusion: Vocational school students have a low level of adherence. Factors supporting non-adherence were perceived side effects and family support.